The effect of virtual reality on patients’ experiences of pain during painful wound care procedure: a systematic review and meta-analysis of randomized controlled trials - Çetinkaya Özdemir, Serap; Stolt, Minna (BioMed Central, 2026)
Background
Wound care procedures can often cause intense and intolerable pain for patients and negatively affect their quality of life.
Objective
This study aimed to determine the impact of virtual reality applied in wound care procedures on pain management.
Methods
A systematic review and meta-analysis. From online databases, including PubMed, ScienceDirect, Scopus, EBSCO (MEDLINE) and Web of Science. Two independent systematic searches of databases were conducted by two researchers. Two independent systematic searches of databases were conducted by two researchers in April 2025. The search strategy was adapted to bibliographic databases. All relevant studies published until the end of April 2025 were included, with no time restrictions applied to capture the earliest research on VR in wound care. Then, two reviewers independently screened literature, and extracted data. After conducting a quality assessment of the included literature, meta-analysis was performed. The degree of heterogeneity was also indicated by using I2statistic.
Results
This systematic review and meta-analysis included seven randomized controlled trials. The results of the studies included in the systematic review revealed that VR effectively reduced pain during dressing changes, as reported in most included studies. However, our meta-analysis for pain, based on three studies, revealed substantial heterogeneity (I2 = 86.19%) and did not show a statistically significant overall reduction in pain scores. Similarly, the meta-analysis for anxiety, derived from two studies, showed no heterogeneity (I2 = 0%) and did not yield a statistically significant pooled effect for anxiety reduction.
Conclusion
Virtual reality shows promise in reducing pain during a wound care procedure. However, large-scale methodologically sound randomized controlled trials are recommended to determine its efficacy in reducing post-procedural pain and anxiety and its broader effect on vital signs.